(untitled) - Vičarová, Eva (Aura musica, 2019)
The study presents musical experiment lead by students from Palacký University in Olomouc and his tutor. The research team worked with high school - and university Youth. The main idea of the experiment was inspired by Otakar Hostinský's book On the Socializing of the Arts (Prague 1903). Five compositions represented the music of the second half of the 20th century as well as contemporary classical music (O. Messiaen, K. Penderecký, K. Husa, V. Zouhar and R. Hejnar). The main aim of the project - to improve the reception of these works - was successful.
Keywords: music preferences; music experiment; secondary grammar school students; university students; 15-20 years old Youth; classical music of the 2nd half of the 20th century; contemporary classical music